Global Cities At Work New Migrant Divisions of Labour - Evans, Yara (Pluto Press, 2009)
This book is about the people who always get taken for granted. The people who clean our offices and trains, care for our elders and change the sheets on the bed. Global Cities at Work draws on testimony collected from more than 800 foreign-born workers employed in low-paid jobs in London during the early years of the twenty-first century. This book breaks new ground in linking London's new migrant division of labour to the twin processes of subcontracting and increased international migration that have been central to contemporary processes of globalisation. It also raises the level of debate about migrant labour, encouraging us to look behind the headlines. The authors ask us to take a politically informed view of our urban labour markets and to prioritise the issue of poverty in underemployed communities.